A review of the asilid (Diptera) fauna from Hispaniola with six genera new to the island, fifteen new species, and checklist - Scarbrough, Aubrey G.; Perez-Gelabert, Daniel E. (Zootaxa, 2006)
The robber fly fauna of the 6 subfamilies Apocleinae, Asilinae, Laphrinae, Ommatiinae, Stenopogoninae, and Trigonomiminae of Hispaniola with special reference to the Dominican Republic is reviewed in light of new collections. This paper reports 6 genera (Cerotainia Schiner,   Eumecosoma Schiner, Holcocephala Jaennicke, Pilica Curran, Proctacanthella Bromley, and Rhopalogaster Macquart) new to the island, increasing the number to 20. Within the West Indies,   Eumecosoma, Holcocephala, Pilica, and Proctacanthella are only known from Hispaniola. Also, 33 species are reported, including 15 new species (Atomosia anacaona, A. ciguaya, A. jagua, A. jimagua, A. yurabia, Cerotainia sola, Eumecosoma caerulum, Holcocephala indigena, Ommatius geminus, O. laticrus, O. maculosus, O. praelongus, Proctacanthella taina, Plesiomma simile, and Rhopalogaster albidus), increasing the number to 62 species plus 2 species in Dominican amber. The male of O. cinnamomeus Scarbrough & females of Plesiomma inflatum and Proctacanthus darlingtoni Curran are reported for the first time. The Ommatius lucidatus species group is established with 8 extant and 2 fossil species. Plesiomma angustum (Macquart) and Atoniomyia mikii (Williston) are rediscovered and redescribed. Plesiomma lineata (Fabricius) is removed from the distribution list for Cuba and Jamaica and Neophoneus is removed from the list of West Indies asilids because of an error in identification. Neophoneus flavotibis Bigot tentatively diagnosed as belonging to the genus Efferia. Plesiomma macra Loew is removed from synonymy. Significant structures of most species are illustrated and keys to selected species are included. At least one species of Atoniomyia and Pilica remain undescribed from this survey. New distribution records for most species and a checklist of the Hispaniolan fauna are also included.